Changes in recreational drug use, reasons for those changes and their consequence during and after the COVID-19 pandemic in the UK - Maria Bălăeţ; Ana Zadel; Anne Lingford-Hughes; Louise M. Paterson; Samuel R. Chamberlain; William Trender; Peter J. Hellyer; Adam Hampshire (Comprehensive Psychiatry)
Changes in drug use in the general population during the COVID-19 pandemic and their long-term consequences are not well understood. We employed natural language processing and machine learning to analyse a large dataset of self-reported rates of and reasons for drug use during the pandemic, along with their associations with anxiety, depression and substance use problems post-pandemic. Our findings revealed a transient decrease in drug use at the pandemic's peak, primarily attributed to reduced social opportunities. Conversely, some participants reported increased drug use for self-medication, boredom, and lifestyle disruptions. While users of psychedelics and MDMA had anxiety and depression rates similar to non-users, users of opioid agonists and depressants—representing one in ten active drug users—reported greater mental health challenges post-pandemic. These results suggest that a subset of active drug users with distinct profiles faces elevated risks, particularly for anxiety and depression, and may benefit from targeted support.